Maternal heart disease and pregnancy complications: a tertiary hospital experience from Turkiye - Karabay, Gülşan; Şeyhanlı, Zeynep; Filiz, Ahmet Arif; Ayhan, Hatice; İpek, Selma and Karabay, Umut and Çağlar, Ali (The European Research Journal, 2025)
Objectives: Maternal heart disease is a leading cause of non-obstetric maternal mortality and morbidity, complicating the necessary physiological changes during pregnancy. This study aimed to evaluate maternal and perinatal outcomes in pregnancies complicated by maternal heart disease. Methods: A retrospective analysis was conducted from November 2022 to November 2023 at a tertiary care hospital. Ninety-three pregnant women with maternal heart disease were included and categorized into congenital heart disease, rheumatic heart disease, and other cardiac conditions. Data on demographics, obstetric complications, and perinatal outcomes were analyzed. Results: Among the participants, 47.3% had rheumatic heart disease, 37.6% had other cardiac conditions, and 15.1% had congenital heart disease. Maternal outcomes included a 29% incidence of preterm delivery, and an 8.6% occurrence of fetal growth restriction, and 7.5% of mothers requiring postpartum intensive care. However, no maternal mortality was observed. Neonatal outcomes included a 30.3% admission rate to the neonatal intensive care unit and a 12.9% incidence of respiratory distress syndrome, with no recorded fetal mortality. Outcomes were consistent across the three cardiac disease groups, demonstrating the effectiveness of multidisciplinary care approaches. Conclusions: Early diagnosis, individualized care, and multidisciplinary management are essential for improving outcomes in pregnancies with maternal heart disease. Despite no observed maternal or fetal mortality, high rates of preterm births and neonatal complications emphasize the need for targeted interventions. Addressing modifiable risk factors like hypertension and obesity is critical. Multicenter studies with larger cohorts are recommended to enhance management strategies.